2019
DOI: 10.1242/jeb.196188
|View full text |Cite
|
Sign up to set email alerts
|

Threshold effect in the H2O2 production of skeletal muscle mitochondria during fasting and refeeding

Abstract: Under nutritional deprivation, the energetic benefits of reducing mitochondrial metabolism are often associated with enhanced harmful pro-oxidant effects and a subsequent long-term negative impact on cellular integrity. However, the flexibility of mitochondrial functioning under stress has rarely been explored during the transition from basal non-phosphorylating to maximal phosphorylating oxygen consumption. Here, we experimentally tested whether ducklings (Cairina moschata), fasted for 6 days and subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…However, the two subsequently-activated components in this biochemical cascade, the H2O2-scavenging enzymes, failed. The absence of an adequate response from CAT and GSH-Px in removing H2O2 is in agreement with the significant increases in H2O2 concentrations that are observed during fasting in the mitochondria of different animals (Sorensen et al, 2006;Salin et al, 2018;Roussel et al, 2019). Aside from direct effects, such as oxidative damage of biomolecules, it was suggested that increased H2O2 concentration as a secondary messenger could play a role in the re-feeding signal (Sylvie et al, 2012) by modulating cellular hormesis (Costantini, 2014;Schull et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…However, the two subsequently-activated components in this biochemical cascade, the H2O2-scavenging enzymes, failed. The absence of an adequate response from CAT and GSH-Px in removing H2O2 is in agreement with the significant increases in H2O2 concentrations that are observed during fasting in the mitochondria of different animals (Sorensen et al, 2006;Salin et al, 2018;Roussel et al, 2019). Aside from direct effects, such as oxidative damage of biomolecules, it was suggested that increased H2O2 concentration as a secondary messenger could play a role in the re-feeding signal (Sylvie et al, 2012) by modulating cellular hormesis (Costantini, 2014;Schull et al, 2016).…”
Section: Discussionsupporting
confidence: 63%
“…The shading of each region represents whether oxygen is put toward ATP production (slashed region), proton leak (filled gray region), or ROS production (unshaded region). In (A), the filled circles represent possible measurements of an animal at rest (i) or the same animal in a state of high activity (ii), informed by data in [79]. In a highly active state (ii), the high demand for ATP causes ATP synthase to rapidly use up the proton gradient, so protonmotive force and rate of proton leak become relatively low.…”
Section: Illustration Of Within-and Among-individual Variation In Mit...mentioning
confidence: 99%
“…This condition promotes succinate accumulation within mitochondria (Hochachka et al, 1975), and thereafter a burst of reactive oxygen species production that is associated with its rapid oxidation during post-dive reperfusion of tissues (Dröse, 2013). Again, the phosphorylating activity of mitochondria negatively regulates the ANT-mediated fatty acid-induced proton leak (Roussel et al, 1998(Roussel et al, , 2000Bertholet et al, 2019) and the release of reactive oxygen species from mitochondria (Goncalves et al, 2015;Roussel et al, 2019), which would in turn prevent the activation of UCPs. These properties indicate that the uncoupling activities of ANT and avUCP would be at a minimum under high phosphorylating activity when mitochondria are fully coupled and cellular energy demand is high, but maximum in a resting state when mitochondria are loosely coupled and cellular energy demand is low.…”
Section: Molecular Hypothesis On the Mechanism Connecting Coupled And Uncoupled Energy Conversion In Mitochondriamentioning
confidence: 99%